Teachers' well-being in times of Covid-19 pandemic: factors that explain professional well-being - Alves, Regina Ferreira (2021)
This cross-sectional study was aimed to describe and analyse factors related to the professional well-being of Portuguese teachers during the COVID-19 pandemic. A previously validated, anonymous and online questionnaire was applied to a non-probabilistic sample of Portuguese teachers. In addition to the socio-demographic and professional variables, the questionnaire measured subjective and professional well-being, satisfaction with the education system and future perspectives regarding the professional circumstances. The psychometric characteristics of the questionnaire were analysed, the t-test and ANOVA were used to analyse the differences between the main variables and the socio-demographic and professional characteristics, along with the generalized linear model in order to more precisely determine the predicting factors of teachers' professional well-being. The results showed that the majority of respondents have a moderately positive perception of well-being. Teachers were satisfied with the education system before the pandemic. The pandemic has reduced the perception of well-being in the face of the profession, creating some concern among teachers about their professional future. Sex, length of service, well-being, perceptions of teaching difficulties and future perspectives proved to be predictors of professional well-being in times of pandemic. This study provided scientific bases for the development of interventions that improve the professional well-being of teachers, which focus on emotional management and the development of digital skills in teachers with long careers. This piece of research concluded with thorough evidence that there is a need for further and stronger investment in public policies for the reform and, consequently, for the renewal of the teaching class.